Research in biologically active substances of the volatile fraction from Highbush blueberry vegetative organs - O. O. Stremoukhov; O. M. Koshovyi; M. A. Komisarenko (Zaporozhye State Medical University, 2021)
Ukraine ranked second in the world after Peru in the pace of laying new Highbush blueberry plantations. Experts estimate that in 2018, in Ukraine, from 0.7 thousand hectares to 1.0 thousand hectares of new Highbush blueberry plantations were laid. Over the past 12 years, previously little-known product, Highbush blueberries have become one of the main berry crops. At present, commercial plantations blueberries take the 3rd place after black currants and strawberries. Zhytomyr region boasts the biggest areas planted with Highbush blueberries in Ukraine, followed by Volyn and Kyiv. According to estimates, the export of blueberries from Ukraine may increase to 20 thousand tons in 5 years. In addition to the use of Highbush blueberries in the food industry, they are a promising source of BAS for pharmaceutical and medical use, so their study is a promising area of pharmaceutical science. In Ukraine, there are no domestic standardized medicines manufactured from Highbush blueberries, and there are only foreign dietary and functional supplements. Abroad, Highbush blueberry medicines are used to improve vision and as astringents for colitis, enterocolitis and diarrhoea. In this regard, the development of domestic standardized medicines based on Highbush blueberries raw materials is an urgent task for modern pharmacy. The aim of the research was to study the phytochemical profile of the volatile fraction of Highbush blueberry vegetative organs (leaves, stems and fruits). Materials and methods. The objects of research were the leaves, fruits and stems of Highbush blueberry (Vaccinium corymbosum L.), in which the composition of the the volatile fraction components was studied by chromato-mass spectrometry on a gas chromatograph Agilent Technologies 6890 with a mass spectrometric detector 5973. Results. Chromato-mass spectrometry in the composition of volatile fractions of leaves, fruits and stems of Highbush blueberries revealed 65 substances. 49 substances were identified in the Highbush blueberry leaves, of which 36 substances of terpene nature, 13 organic acids, and 2 compounds were not identified. In the Highbush blueberries fruits, 47 substances were found, of which 36 substances are of terpene nature, 14 are organic acids and 3 were not identified. In the Highbush blueberries stems, 50 substances were found, of which 33 substances are of terpene nature, 14 are organic acids and one was not identified. Conclusions. As a result of phytochemical studies, it is for the first time that the component composition of volatile fractions of leaves, stems and fruits of Highbush blueberries from the flora of Ukraine was established. The content of 65 substances was identified and established, including 14 organic acids and 39 terpene compounds.